Mortality from non-neoplastic digestive diseases in the adult population of Peru, 2010 - 2015 - Castillo-Contreras, Ofelia (2019)
Introduction. Non-neoplastic digestive diseases (DD) are important causes of medical consultation and hospitalization. Objective. To determine the mortality by non-neoplastic DD in the adult population of Peru between 2010 and 2015. Methods. Secondary analysis of the registry of non-neoplastic DD deaths in the population over 18 years old between 2010 and 2015 of the General Office of Statistics and Informatics of the Ministry of Health of Peru. The population for the same period was obtained from the National Institute of Statistics and Informatics. The standardized mortality rates (SMR x 100 000 person-years) were calculated. Results. During the period 2010-2015 there were 39 889 deaths due to non-neoplastic DD. The highest SMR were for the group of liver diseases (12,2 x 100 000 person-years), with fibrosis and cirrhosis of the liver having the highest mortality (9,1). Acute pancreatitis (1,0) had higher SMR than gastric ulcer (0,7). The SMR, according to the regions of Peru, were high due to fibrosis and cirrhosis of the liver in Piura (16,3), Lambayeque (14,6) and La Libertad (14,4); by cholelithiasis (1,1) and acute cholecystitis (1,7), in Puno; for acute pancreatitis (2,2), in Tacna; and gastric ulcer was higher in Huancavelica (3,6) and Huánuco (2,3). Conclusions. Liver fibrosis and cirrhosis was non-neoplastic DD with a higher mortality rate in the adult population of Peru, mainly in the northern coast of the country.